Compras públicas sustentáveis: um estudo de caso do processo decisório em órgãos federais do Rio de Janeiro - Souza, Carla Oliveira de (2016)
This research aims to describe the factors that influence the decision-making process on the shared sustainable purchasing between public sector agencies. For this purpose, a case study research has been made in which the same process was analyzed under different perspectives, using the theoretical approach of rational models, organizational and political for decisionmaking analysis. Methodologically, the research was an exploratory-descriptive and the data collected from desk research and the interviews have been analyzed through content analysis using analytical categories. The results reveal a complex decision-making process in which there are rational factors, organizational and political. The rational factors identified were: rational choice, bounded rationality and value maximization. The first has been the least perceived factor in comparison to the others. The organizational factors observed were: patterns and organizational processes, adaptation and organizational learning, predictability and organizational culture. The latter exercised little influence in decision making. The political factors identified were: power, interest, external influence, cooperation and coalition, negotiation and persuasion and conflict. The latter two are less noticeable compared to the other. Furthermore, it was found that the process of sustainable purchase decision making is especially rational and organizational, as a normative point of view, but it is also political in its development. Finally, the use of patterns and organizational processes that lead to sustainable practice in public organizations seems to be the most important factors identified because, while serving as a normative support, standardizes behaviors, bringing changes in organizational culture.